72 THE EPIDEMIOLOGY, HERITABILITY, AND GENETIC LINKAGE OF C-REACTIVE PROTEIN IN THE JACKSON HEART STUDY. Issue 1 (1st January 2007) - Fox, E. R.; Benjamin, E. J.; Sarpong, D. F.; Rotimi, C. N.; Wilson, J. G.; Taylor, J. K.; Taylor, H. A.
Abstract : Purpose: There is limited information on CRP's reference ranges, heritability, and relation to cardiovascular disease (CVD) risk factors and disease in African Americans. Methods: The study consists of participants who underwent Exam 1 of the Jackson Heart Study (2001-2004). The distribution and correlates of CRP were analyzed for the entire study cohort. Heritability was estimated for the family cohort nested within the larger JHS (235 families, n = 1, 364). The relations between CRP and traditional CVD risk factors were tested with multivariable stepwise regression analyses. Heritability was estimated using mixed-model regression analysis. QTL linkage analysis was performed using the multipoint variance components approach in SOLAR package. Results: The study cohort consisted of 5, 202 participants (55 ± 13 years, 64% female). The median CRP was 2.7 mg/L. In stepwise models traditional risk factors explained 23% of the variability of CRP, with BMI (partial R 2 = 12.9%) explaining 57% of the variability of CRP due to traditional risk factors. The heritability for the age-, sex-, and BMI-adjusted CRP residual after winsorizing was 0.37, with a standard error (SE) of 0.06, and the heritability for the log transformed CRP residual was 0.45, with a SE of 0.06. The strongest evidence for linkage to CRP was observed on chromosome 3 (maximum LOD score of 2.92) near marker 295YC9P and chromosome 12 (maximum LOD score of 2.01) near marker D12S297. Conclusion: In this large population-based cohort of African Americans, CRP concentrations were heritable and associated with several traditional cardiovascular risk factors, particularly with elevated BMI. Given the relationship between inflammation and CVD, further research into the genetic and environmental determinants of CRP is merited.